Metodología de cálculo para el estudio termodinámico de las instalaciones de secado, del proceso de fabricación de levadura torula - Cabrera Sánchez, Jorje L.; Puerta Fernández, Juan F.; González Pérez, Félix (Centro Azúcar Journal, 2008)
In this paper, is presented a methodology for the calculation of the main parameters of a process of yeast drying. This procedure uses a small number of data and it is based on the thermodynamic principles. The operations are evaluated under the conditions of the drying process. Also, it is presented the experiences of a Cuban plant of yeast processing, and its improvements in energy saving.